Логистическое управление запасами в формировании ассортиментной политики предприятия - Шквыря, Наталья Александровна; Шквиря, Наталя Олександрівна; Shkvyria, Natalia (My University, 2019)
RU: В статье рассмотрены вопросы оптимизации ассортиментной политики предприятия на основе ABC-XYZ-анализа. Раскрыта сущность и значение метода ABC-XYZ-анализа для формирования ассортиментной политики предприятия. С помощью ABC-XYZ-анализа проанализирована ассортиментная политика исследуемого предприятия и сформулированы рекомендации по ее усовершенствованию. Определено, что использование АВС и XYZ-анализа позволяет оценить весь ассортимент предприятия и понять, как можно управлять теми или иными группами и категориями продукции. EN: The article deals with optimization of the enterprise product assortment policy based on ABC-XYZ analysis. The essence and significance of the ABC-XYZ analysis method for forming the enterprise assortment policy are disclosed. With the help of ABC-XYZ-analysis the assortment policy of the studied enterprise is analyzed and recommendations for its improvement are formulated. It is determined that the use of ABC and XYZ analysis allows to evaluate the whole range of the enterprise and to understand how it is possible to manage these or other groups and categories of products.
Keywords: ассортиментная политика; ABC-анализ; XYZ-анализ; логистическое управление; assortment policy; ABC analysis; XYZ analysis; logistics management